Community Engagement in a complex intervention to improve access to primary mental health care for hard‐to‐reach groups. (29th September 2014) - Lamb, Jonathan; Dowrick, Christopher; Burroughs, Heather; Beatty, Susan; Edwards, Suzanne; Bristow, Kate; Clarke, Pam; Hammond, Jonathan; Waheed, Waquas; Gabbay, Mark; Gask, Linda
Abstract: Background: Despite the availability of effective evidence‐based treatments for depression and anxiety, many 'harder‐to‐reach' social and patient groups experience difficulties accessing treatment. We developed a complex intervention, the AMP (Improving Access to Mental Health in Primary Care) programme, which combined community engagement (CE), tailored (individual and group) psychosocial interventions and primary care involvement. Objectives: To develop and evaluate a model for community engagement component of the complex intervention. This paper focuses on the development of relationships between stakeholders, their engagement with the issue of access to mental health and with the programme through the CE model. Design: Our evaluation draws on process data, qualitative interviews and focus groups, brought together through framework analysis to evaluate the issues and challenges encountered. Setting & participants: A case study of the South Asian community project carried out in Longsight in Greater Manchester, United Kingdom. Key findings: Complex problems require multiple local stakeholders to work in concert. Assets based approaches implicitly make demands on scarce time and resources. Community development approaches have many benefits, but perceptions of open‐ended investment are a barrier. The time‐limited nature of a CE intervention provides an impetus to 'do it now', allowing stakeholders to negotiate their investment over time and accommodating their wider commitments. Both tangible outcomes and recognition of process benefits were vital in maintaining involvement. Conclusions: CE interventions can play a key role in improving accessibility and acceptability by engaging patients, the public and practitioners in research and in the local service ecology.